Epidemiology of leptospirosis in Groote Schuur Hospital - Mteshana, Ziningi Charity (Department of Medicine, 2021)
Background The burden of leptospirosis in sub-Saharan Africa remains unclear although it is accepted that this infection is widely spread in this region. The global estimated number of cases is one million with 58 900 deaths attributable to leptospirosis annually. Objective To describe the profile of patients with suspected leptospirosis and to compare their in hospital outcomes. Methods & Material We performed a retrospective study at a tertiary referral hospital in South Africa. All adults with suspected leptospirosis who had a laboratory request for leptospirosis ELISA IgM testing between 2005 and 2015 were included. Clinical and laboratory findings at presentation were correlated with the patient's subsequent clinical course and ELISA IgM status. Results During the study period 223 patients who had ELISA IgM test requests were enrolled. Leptospirosis ELISA IgM was positive in 45 (20%) patients. Enrolled patients had a median age of 38 (IQR 31 – 53) years, 147/223 (66%) were males and 80/223 (36%) were HIV positive. There were 12/45 (27%) HIV-positive patients in the IgM-positive group compared to 68/178 (38%) in the IgM-negative group, p=0.22. Compared to IgM-negative patients, patients with positive IgM were more likely to present with jaundice 37/45 (82%) vs. 82/178 (46%), p <0.01, and acute kidney injury (AKI) 34/45 (76%) vs.102/178(57%), p=0.06. The median length of hospital stay was 13 days (IQR 8-22 days) for IgM-positive compared to 10 days (IQR 6-21 days) in IgM-negative patients, p= 0.10. A total of 11/45 (24%) IgMpositive patients required ICU admission compared to 41/178 (23%) of IgM-negative patients, p=0.84 and the median length of ICU stay was 7 days (IQR 4-11) for IgM-positive compared to 6 days (IQR 3-9.5) for IgM-negative patients, p=0.51. There were 13/45 (29%) IgM-positive patients who needed dialysis compared to 42/178 (24%) of IgM-negative patients, p= 0.46. The mortality rate was 7/45 (16%) in IgM-positive compared to 52/178 (29%) in IgM-negative patients, p=0.07. Conclusion Patients with positive IgM presented predominantly with jaundice and AKI. There was no statistically significant difference in HIV status and outcomes between the two groups of patients